Synthesis, Spectral, Thermal and Structural Characterization of the Copper(II) Saccharinato Complex of 2-aminopyrimidine, [Cu(sac-O)(2)(ampym-N)(2)(H2O)2] 2ampym - Yesilel, OZ; Ölmez, H; Pasaoglu, H; Kastas, G; Büyükgüngör, O (Walter de Gruyter GmbH, 2006)
Bis(2-aminopyrimidine-N)diaquabis(saccharinato-O)copper(II) di(2-aminopyrimidine), [Cu(sac-O)(2)(ampym-N)(2)(H2O)(2)]center dot 2ampym was synthesized and characterized by means of elemental analysis, IR and UV-vis spectroscopy, magnetic susceptibility, simultaneous TG, DTG, DTA techniques, and X-ray diffraction. The complex crystallizes in the monoclinic space group P2(1)/c [a=7.4697(5), b=10.1679(5), c=22.743(2) angstrom, beta=92.844(5), Z=2, R=0.0275, wR=0.0757, V=1725.26(19) angstrom(3)]. The copper atom is bonded to two ampym N atoms and two sac O atoms as well as to two water O atoms in trans positions in the geometry of a distorted octahedron. There are also two ampym moieties as solvate molecules in the unit cell. The crystal structure is stabilized by N-H center dot center dot center dot O, O-H center dot center dot center dot N and C-H center dot center dot center dot O type hydrogen bonding interactions. Intermolecular pi-pi interactions between the phenyl rings of ampym groups and C-H center dot center dot center dot pi interactions also support the packing of the molecules. The thermal decomposition of the complex has been studied.
Yeşi̇lel, Okan Zafer/0000-0002-2284-1578
Keywords: Copper(II) Complex; Saccharinato Complex; 2-Aminopyrimidine; Thermal Studies